Comparative analysis of nafta and nafta Colombia - United States: impacts in the agricultural sector (2017)
The Mexican experience of NAFTA offers the opportunity to compare the economic policies that the Free Trade Agreements use and the impacts they have. In that sense, a parallel is made between the Mexican case and the Colombian case, in order to establish similarities in the negotiations and the impacts of the same in the countries that have reached trade agreements with the United States, as in the case of Mexico and Colombia. To address this theme, agriculture will be taken as the focus of study, pointing to asymmetry as a prominent feature in trade agreements signed by these countries.